Genetically-encoded targeted protein degradation technology to remove endogenous condensation-prone proteins and improve crop performance - Ming Luo; Sitao Zhu; Hua Dang; Qing Wen; Ruixia Niu; Jiawei Long; Zhao Wang; Yongjia Tong; Yuese Ning; Meng Yuan; Guoyong Xu (Nature Communications)
Abstract Effective modulation of gene expression in plants is achievable through tools like CRISPR and RNA interference, yet methods for directly modifying endogenous proteins remain lacking. Here, we identify the E3 ubiquitin ligase E3TCD1 and develope a Targeted Condensation-prone-protein Degradation (TCD) strategy. The X–E3TCD1 fusion protein acts as a genetically engineered degrader, selectively targeting endogenous proteins prone to condensation. For example, a transgenic E3TCD1 fusion with Teosinte branched 1 (TB1) degrades the native TB1 protein, resulting in increased tiller numbers in rice. Additionally, conditional degradation of the negative defense regulator Early Flowering 3 via a pathogen-responsive ProTBF1-uORFsTBF1 cassette enhances rice blast resistance without affecting flowering time in the absence of pathogen. Unlike prevailing targeted protein degradation strategies, the TCD system does not rely on small molecules, antibodies, or genetic knock-in fusion tags, demonstrating its promise as a transgene-based approach for optimizing crop performance.